Correlation Between Emotional Intelligence and Students' Achievement in Learning English - Hasibuan, Robiatul; Irwandi, Irwandi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
This research explores the correlation between emotional intelligence and students' achievements in learning English. A correlation study was conducted on 34 students in Grade X of Pesantren Al-Amin Mompang Padang Lawas in the year 2023. Data were collected through a questionnaire and documentation of students' English achievement. Spearman Level Correlation calculated the correlation coefficient (Ï) to determine the relationship between the two variables. It was concluded that there was a positive correlation (Ï = 0.78) between emotional intelligence and students' achievement in learning English, indicating that emotional intelligence has a high influence on the achievement of students in learning English. The result of t-test (t-test = 0.78 > 0.52) accepted the hypothesis, which states there is a significant correlation between emotional intelligence and students' learning achievement in English.